Tinjauan Kemampuan Tenaga Kesehatan pada Pengelolaan Sistem Informasi Kesehatan (SIK) Di Puskesmas Sulamadaha Kecamatan Pulau Ternate Tahun 2013 - Samad Hi Husen; Irma B Lewa (Jurnal Kesehatan, 2014)
Abstract : Health information system is an information management at all levels of government systematically for service delivery to the public. Legislation that mentions the health information system is Kepmenkes No. 004/Menkes/SK/I/2003 on the policy and strategy of decentralization in health and Kepmenkes No. 932/Menkes/SK/VIII/2002 on the implementation of the instructions of health information reporting system development district / the city. It's just the two of contents Kepmenkes contains weaknesses which are both just looked at the health information system from the point of the field of health management, do not utilize state of the art technology and no information relating to the national information system. Information and communication technology are also not yet elaborated so that the data presented are not appropriate and not timely. Based on the background of the problem, it can be argued formulation of the problem "How Ability Health Workers In SIK in PHC Sulamadaha Management District of Ternate Island" viewed from the aspect of education and training, motivation, and work experience. General Purpose To determine the ability of health professionals in the management of health information in health centers Sulamadaha District of Ternate Island. Specific Objectives To determine the ability of health professionals in the management of health information in health centers Sulamadaha District of Ternate Island in terms of aspects of education and training, to determine the ability of health personnel in the management of health information in health centers Sulamadaha District of Ternate Island viewed from the aspect of motivation and to determine the ability of health personnel in the management of SIK The PHC Sulamadaha District of Ternate Island viewed from the aspect of work experience.